Impact of postharvest calcium chloride treatments on decay rate and physicochemical quality properties in strawberry fruit - Deniz Eroğul; Muttalip Gundogdu; Fatih Sen; Akgul Tas (BMC Plant Biology)
Abstract Background Post-harvest losses cause significant product losses in the world, which leads to food waste. Therefore, it is of great importance for people to have access to sufficient amounts of products by increasing the storage period of fruits with applications such as post-harvest calcium chloride (CaCl2). In this study, the effect of calcium chloride (CaCl2) on physical quality parameters and bioactive contents of stored strawberry fruit (Albion cv.) was investigated. Accordingly, strawberries were treated with 2%, 4% and 6% CaCl2 before storage and stored for 15 days (0 ± 0.5 °C and 90 ± 5% RH). Analyses and measurements were conducted every 5 days during the storage period.Weight loss, decay rate, soluble solids content (SSC), acidity, pH, respiration rate, organic acids (malic, citric, ascorbic, fumaric, oxalic, succinic and tartaric) and phenolic compounds (catechin, chlorogenic, ferulic, gallic, o-coumaric, p-coumaric, protocatechuic, quercetin, rutin and syringic) were analyzed as quality parameters during storage. Results In the study, in general, the best values were observed in 6% CaCl2-treated fruits in terms of weight loss, SSC, TA, decay and respiration rates, although they varied according to different storage periods. Similarly, in terms of phenolic compounds, organic acids and vitamin C, 6% CaCl2-treated fruits had significantly better prevention of quality losses. In addition, the most common phenolic compound of strawberry fruits was gallic acid, followed by chlorogenic acid and catechin, respectively. On the other hand, the predominant organic acid observed in the fruits was malic acid, followed by citric acid, succinic acid and oxalic acid, respectively. Conclusions In this study, it was observed that CaCl2 applications more effectively prevented weight loss and decay rate by reducing the respiration rate compared to the control group at the end of the storage period (15th day). It was concluded that, particularly, the 6% CaCl2 dose can be used as an important treatment to extend storage life by preserving fruit quality and biochemical changes.